Capital asset pricing model - Takouachet, Rania (Finance and Business Economies Review, 2020)
This study aims to identify the model of capital asset pricing (CAPM), which occupies a privileged position in the stock market because it is one of the analysis tools that take into account the relationship between return and risk in securities and capital investments in general. Which is considered one of the most important discoveries in the modern financial economy where despite the many criticisms of this model, the basic model has simplicity, speed and ease. This feature has kept this model in use today and on a large scale by most specialists in the financial field.